2008
DOI: 10.1016/j.intell.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Which working memory functions predict intelligence?

Abstract: Investigates the relationship between three factors of working memory (storage and processing, relational integration, and supervision) and four factors of intelligence (reasoning, speed, memory, and creativity) using structural equation models. Relational integration predicted reasoning ability at least as well as the storage-and-processing construct. Supervision, measured as specific switch costs, was not related to intelligence, but general switch costs were moderately correlated to the reasoning factor. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
238
2
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(274 citation statements)
references
References 38 publications
26
238
2
8
Order By: Relevance
“…The idea that there are multiple sources of variance underlying general cognitive abilities such as working memory capacity and intelligence has a long history (e.g., Thurstone, 1931Thurstone, , 1938 and is consistent with multi-component models of working memory (Baddeley & Hitch, 1974), as well as prior investigations of individual differences in working memory capacity that have posited multiple pools of resources (Daneman & Tardiff, 1987;Shah & Miyake, 1996). Indeed, the current results are consistent with the notion that there are multiple sources of variation across both task domains and cognitive processes (Conway & Kovacks, 2013;Logie, 2011;Oberauer, Süss, Wilhelm, & Wittmann, 2008).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The idea that there are multiple sources of variance underlying general cognitive abilities such as working memory capacity and intelligence has a long history (e.g., Thurstone, 1931Thurstone, , 1938 and is consistent with multi-component models of working memory (Baddeley & Hitch, 1974), as well as prior investigations of individual differences in working memory capacity that have posited multiple pools of resources (Daneman & Tardiff, 1987;Shah & Miyake, 1996). Indeed, the current results are consistent with the notion that there are multiple sources of variation across both task domains and cognitive processes (Conway & Kovacks, 2013;Logie, 2011;Oberauer, Süss, Wilhelm, & Wittmann, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…These findings support multiple source theories of capacity and intelligence and are inconsistent with general ability models (cf., Conway & Kovaks, 2013;Logie, 2011;Oberauer et al, 2008). The current study failed to replicate certain aspects of Fukuda et al (2010) with respect to the relationship between number and resolution measures derived from visual array tasks.…”
Section: Discussioncontrasting
confidence: 68%
“…Second, trivia quiz questions could evoke reasoning strategies (e.g., rejection of implausible answers) that would require -and hence, practice -relational integration processes; that is, the coordination of information elements into structures. Recent theories consider relational integration as crucial part of WM (e.g., Oberauer, 2010;Oberauer, Süß, Wilhelm, & Wittmann, 2003), and research has shown that such processes are highly related to fluid intelligence (e.g., Oberauer, Süß, Wilhelm, & Wittmann, 2008). We can only speculate whether such processes took place during active control training, but it could serve as an explanation for the active control group also showing some improvement in the transfer tasks.…”
Section: Discussionmentioning
confidence: 86%
“…However, the present study can serve as a basis for future research putting shifting ability into the wider context of cognitive performance. More specifically, shifting has often been found to show different or even opposing patterns of correlations with other cognitive abilities (e.g., fluid intelligence) than other but supposedly related executive functions such as working memory (e.g., Oberauer, Süß, Wilhelm, & Wittmann, 2008; but see Draheim, Hicks, & Engle, 2016, for a possible methodological explanation), or inhibition and common executive function (cf. Miyake & Friedman, 2012).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%